Knowledge of Dengue Hemorrhagic Fever Prevention Among 5th and 6th Grade Elementary School Students in Sambi District, Boyolali - Listiana Listiana,; Fida’ Husain, (International Journal Of Health Science, 2025)
Background: Dengue Hemorrhagic Fever (DHF) remains a significant public health issue in Indonesia. In 2024, Boyolali Regency recorded 963 DHF cases, with Sambi District accounting for the highest number (114 cases and 1 death). Notably, 16% of cases occurred in school-aged children, highlighting the importance of their knowledge regarding DHF prevention. Objective: This study aimed to assess the level of knowledge about DHF prevention among 5th and 6th grade elementary school students in Sambi District and identify influencing factors. Method: A quantitative descriptive design was applied using a cluster random sampling technique. A total of 62 students from nine elementary schools participated. Data were collected using a validated and reliable questionnaire. Results: The majority of students (64.5%) had moderate knowledge about DHF, 24.2% demonstrated good knowledge, and 11.3% had poor knowledge. Most respondents were female (62.9%). Conclusion: The overall knowledge level among students was categorized as moderate, with a predominance of female respondents. The results indicate the need for enhanced school-based health education programs to improve students’ understanding and preventive practices related to DHF.